PUBLICATION PRODUCTIVITY, FOCUS ON INSTITUTIONAL, COLLABORATIVE AND COMMUNICATIONAL CORRELATES: A REVIEW OF LITERATURE - A.N., Zainab (Malaysian Journal of Library and Information Science, 2000)
Review studies on academic research assessment comprising: the counting of publication output, citation counts, weighting publications, peer ratings, recognition and multiple indicators. Also describes institutional correlates of publication productivity such as funding, library resources and electronic support. Studies on other correlates such as collaboration, information use and dissemination are also described.